Impact of School Requirements on Pupils’ Academic Performance (Journal of Education and Development, 2019)
This study examines the influence of some school requirements (textbooks, writing materials, school wear and farm tools) on pupils’ academic performance in urban and rural schools in Kumba III sub Division in the Southwest Region of Cameroon. The study used a cross-sectional survey design and a semi-structured Likert-type questionnaire to collected data from class six pupils. Data was analyzed descriptively using frequency, proportion and Multiple-Response Analysis (MRA). To analyse the hypotheses, the perceptions between those that agreed and disagreed were compared using the Chi-Square test of independence. The findings of study showed that generally pupils did not have any of the required learning materials in sufficient quantities and this seriously affected their academic performance. However, pupil’s performance is slightly better in rural areas as children from rural schools possessed slightly more learning materials in comparison to their peers from urban schools. It is recommended that government should increase efforts aimed at ameliorating the living conditions of the populations while international partners (UNICEF, UNESCO) and non-governmental organizations use every means possible to assist government efforts to address and improve this very critical situation and thus enable the pupils to improve their academic performance.